Short-term Tillage and Fertilization Impacts on Soil Organic Carbon, Aggregate Stability and Yield of Soybean-Wheat System in Deep Black Soils of Central India - K.K. Bandyopadhyay, K.M. Hati, R.S. Chaudhary, M. Mohanty, A.K. Biswas and (Journal of the Indian Society of Soil Science, 2015)
In order to study the effect of tillage and nutrient management practices on soil organic carbon (SOC) stock, depth-wise distribution of soil aggregates and yield of the soybean and wheat crops, a field experiment was conducted during 2005–2007 at the experimental farm of the Indian Institute of Soil Science, Bhopal with two tillage treatments namely, no-tillage (NT) and conventional tillage (CT) and five nutrient management practices, such as NPK, NPK+FYM (farmyard manure), NPK+WR (wheat residue), FYM alone and WR alone. The results indicated that SOC concentration of the top 15 cm soil depth and SOC stock of the top 30 cm soil increased significantly under NT compared to CT. Soil organic C stock of the top 30 cm soil was 9.2 per cent higher under NT compared to CT practice. The proportion of macroaggregates (> 250 µm) was also increased by 6.1 and 2.7 per cent, respectively under NT compared to CT system in 0-5 and 5-15 cm soil layers. However, the proportion of microaggregates (53-250 µm) did not show any significant difference in both layers. Among the nutrient management treatments, SOC concentration and relative proportion of macroaggregation was significantly higher in all four treatments where organic matter in the form of either FYM or wheat residues were added compared with NPK treatment in the 0-5 and 5-15 cm layers. The proportion of macroaggregation in organic matter applied plots was 5.2 and 4.5 per cent, higher in 0-5 and 5-15 cm soil layers, respectively compared with the NPK after two cropping cycles. Both the tillage and nutrient treatment differences on SOC concentration and proportion of macroaggregates were not significant in the 15-30 cm soil layer. Soil water storage in the profile did not vary significantly among the tillage treatments during kharif season of 2006. However, profile water storage in NPK, FYM and NPK+FYM was less than the other two nutrient treatments during the later phase of soybean season. The tillage treatments did not show significant effect on yield of both the soybean and wheat crops. Among the nutrient treatments, both soybean and wheat yields were highest in NPK+FYM treated plots and were lowest in the plots under WR alone. The study indicated that short-term no tillage system could improve soil aggregation and SOC concentration of Vertisols in 0-15 cm soil layer while maintaining the yield level similar with the conventional tillage system. Addition of organics along with NPK increased the SOC concentration and aggregation of the soil up to 15 cm soil depth and maintained a higher yield level. The tillage and fertilization treatments did not show any significant interaction effect on crop yields.